No-load tests of a 40 kW high-speed bearingless permanent magnet synchronous motor - Munteanu, G; Binder, A; Schneider, T; Funieru, B (2010 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2010)
A 40 kW high-speed bearingless permanent magnet (PM) synchronous motor with surface mounted magnets represents the focus of this paper. The rotor suspension system is composed of a bearingless unit that generates torque and suspends magnetically the non drive end (NDE) and a permanent magnet biased combined axialradial magnetic bearing for the axial and radial active suspension of the drive end (DE). This drive arrangement has been tested with good performances under no-load conditions at its full speed range. Some basic theory of bearingless drives, the motor main parameters and no-load measurements of the drive and levitation system will be presented.